The Kaniadakis Distribution for the Analysis of Income and Wealth Data - Fabio Clementi (Entropy, 2023)
The paper reviews the “<semantics>κ</semantics>-generalized distribution”, a statistical model for the analysis of income data. Basic analytical properties, interrelationships with other distributions, and standard measures of inequality such as the Gini index and the Lorenz curve are covered. An extension of the basic model that best fits wealth data is also discussed. The new and old empirical evidence presented in the article shows that the <semantics>κ</semantics>-generalized model of income/wealth is often in very good agreement with the observed data.